Pengaruh Lama Perendaman pada Biopriming Padi Anak Daro Menggunakan Bacillus subtilis dan Trichoderma harzianum - Zozy Aneloi Noli; Feskaharny Alamsjah; Riesca Salsabilah Rahmayati (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
The majority of Indonesian people consume rice as a staple food. According to data from the Central Statistics Agency (2022), rice production in West Sumatra reached 1,482,996.01 tons in 2019 and continued to decline until 2021, total rice production in West Sumatra was only 1,317,209.38 tons. This is inversely proportional to the population of West Sumatra which increases every year, so efforts need to be made to increase rice production. One of them is the biopriming technique to increase seed vigor. Priming is hydration carried out slowly which aims to ensure that the seed's water potential reaches balance and activates metabolism in the seed before the seed germinates. One of them is biopriming, which is a seed priming technique using biological agents in the form of beneficial microorganisms. Several factors influence the success of the priming technique, one of which is the soaking time. The right soaking time provides a deeper opportunity to absorb water to stimulate the seeds to germinate. This research aims to determine the effect of soaking time on biopriming of the local West Sumatran rice variety